Analisis Pendekatan Pengembangan Kurikulum dalam Meningkatkan Kualitas Pembelajaran di Lembaga Pendidikan - Khamim, Annisa (Jurnal Kependidikan Islam, 2026)
The curriculum is a fundamental component in the education system that functions as a guideline in the implementation of the learning process. The development of science, technology, and the dynamics of community needs requires the development of a curriculum that is adaptive and relevant to the demands of the times. One of the important aspects of curriculum development is the approach used in the design process. This research aims to analyze various approaches in curriculum development and their implications for improving the quality of learning. The research uses a qualitative approach with the library research method through the study of various literature sources such as books, journal articles, and relevant academic documents. The results of the study show that the curriculum development approach has a strategic role in determining the direction, content, and implementation of learning. Some of the approaches commonly used in curriculum development include the academic subject approach, the humanistic approach, the technological approach, and the social reconstruction approach. Each approach has its own characteristics and contributions in supporting the achievement of educational goals. Therefore, the integration of these various approaches is needed so that the curriculum is able to answer the needs of students and community development more comprehensively.